2022
DOI: 10.3390/plants11050637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nelumbo nucifera Petals Extract on Antioxidant Activity and Sperm Quality in Charolais Cattle Sperm Induced by Mancozeb

Abstract: The white Nelumbo nucifera petals aqueous extraction (NAE) was prominent in phytochemical content, antioxidant activity, and enhanced rat sperm viability induced by FeSO4, a heavy metal. Mancozeb (MZ) contains heavy metals and is widely used for fungal control in agriculture and industry. It induces oxidative stress and causes of spermatogenesis and reproductive organs’ abnormalities in both humans and animals. The aims of the present study were to investigate the effects of white Nelumbo nucifera petals aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…The fine powder of white N. nucifera petals was extracted with hot water at 75-80 • C (1 mg/mL) for 3-5 min. Then, the solutions were filtered and dried by lyophilization with a 12.5% yield [12] and kept at −20 • C until further use in different doses.…”
Section: Plant Collection and Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fine powder of white N. nucifera petals was extracted with hot water at 75-80 • C (1 mg/mL) for 3-5 min. Then, the solutions were filtered and dried by lyophilization with a 12.5% yield [12] and kept at −20 • C until further use in different doses.…”
Section: Plant Collection and Extractionmentioning
confidence: 99%
“…Moreover, histopathological changes in the hippocampus of rats poisoned with chlorpyrifos and cypermethrin, especially pyramidal cells in CA1 and CA3 regions, were induced by stimulating ChE activity and impairing neuron conductivity [53]. Additionally, a recent study showed that white N. nucifera petal extract at a dose of 1.10 mg/kg bw [12] had no toxic effect on the hippocampus structure and learning-memory after oral administration for 30 consecutive days [57]. In view of these and the discussion of the cognitive behavior changes above, further research on the connection between histopathological changes and cognitive behaviors would be helpful in the evaluation of mancozeb and white N. nucifera petal extract effects on brain function.…”
Section: Number Of Pyramidal Cells and Histology Of Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid such negative effects, the inclusion of antioxidants in extenders can minimize the negative effect of ROS and maintain sperm quality after liquid storage (Alenezy et al, 2019). Recently, the protective effect of natural antioxidants on sperm has been largely discussed (Ajuogu et al, 2020; Allai et al, 2018; Laoung‐on et al, 2022; Ros‐Santaella & Pintus, 2021). However, a large list of those studies focused mainly on in vitro assessments, while the information about the fertility results using the natural extracts remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the protective effect of natural antioxidants on sperm has been largely discussed (Ajuogu et al, 2020;Allai et al, 2018;Laoung-on et al, 2022;Ros-Santaella & Pintus, 2021). However, a large list of those studies focused mainly on in vitro assessments, while the information about the fertility results using the natural extracts remains limited.…”
Section: Introductionmentioning
confidence: 99%